Breeding success of Icelandic Pink-footed Geese Anser brachyrhynchus and Greylag Geese A. answer in different areas of Iceland in 1987 and 1988 - Patterson, I J; Giroux, J-F (Wildfowl, 1990)
Brood sizes in Pink-footed Geese and Greylag Geese were measured just after hatching, before fledging and after fledging in south and northeast Iceland in 1987 and post-fledging brood sizes were measured in south, north and northeast Iceland in 1988. In both years brood sizes were also measured after the birds' arrival in Scotland. Brood sizes after hatching were considerably lower than known clutch sizes in both species and Pinkfoot broods continued to decline until after fledging. There was no change in Pinkfoot brood size following migration but Greylag broods were smaller in Scotland than in Iceland in one of the two years of the study. Post-fledging brood sizes did not vary between areas in either species in 1988, or in Pinkfeet, between south and northeast Iceland in 1987. In Greylags, post-fledging brood size in 1987 was significantly higher in south Iceland than in the northeast, where egg harvesting occurred. It is suggested that the lack of any decline in breeding output as the populations of both goose species increased is likely to be due to extension of breeding range into new areas where breeding success was comparable to that in the former range.